2016
DOI: 10.1093/rb/rbv027
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluations of mineralized collagen in the extraction sites preservation

Abstract: The purpose of this study was to explore the different effects between biomimetic mineralized collagen (MC) and ordinary physically blended hydroxyapatite/collagen (HA/Col) composite in evaluating new bone formation and regenerated bone height in human extraction sockets. Thirty-four patients who cannot retain teeth caused by trauma or decay were randomly selected from Department of Stomatology of Dongzhimen Hospital from December 2013 to December 2014. The patients were randomly divided into two groups. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 36 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…It is suggested that three conditions must be present for bone induction to occur: (a) an inducing agent; (b) an osteogenic precursor cell; and (c) an environment that is permissive to osteogenesis (Chai et al, ). In this study, possible explanations for the observed bone regeneration and osseointegration include the following: (a) both bone scaffold materials and titanium implants have the capacity for osteoconduction, and IMC materials have promising effects for osteoinduction (Feng et al, ; Liu et al, ; Zhang et al, ); (b) the blood clot dissolved and/or osteogenic growth factors were secreted from the newly formed vessels in the defect to create an osteoinductive environment; and (c) osteogenic cells were provided by the stumps of the defects.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…It is suggested that three conditions must be present for bone induction to occur: (a) an inducing agent; (b) an osteogenic precursor cell; and (c) an environment that is permissive to osteogenesis (Chai et al, ). In this study, possible explanations for the observed bone regeneration and osseointegration include the following: (a) both bone scaffold materials and titanium implants have the capacity for osteoconduction, and IMC materials have promising effects for osteoinduction (Feng et al, ; Liu et al, ; Zhang et al, ); (b) the blood clot dissolved and/or osteogenic growth factors were secreted from the newly formed vessels in the defect to create an osteoinductive environment; and (c) osteogenic cells were provided by the stumps of the defects.…”
Section: Discussionmentioning
confidence: 92%
“…The difference in new bone formation may be due to differences in the nanostructures of IMC and EMC. Unlike EMC, which is fabricated by a conventional crystallization method and lacks a surface chemistry and nanostructure similar to that of bone extracellular matrix (Hu et al, ; Liu et al, ), IMC is fabricated via a biomimetic strategy to achieve properties that mimic those of native bone (Feng et al, ; Lian et al, ; Liao et al, ; Qiu et al, ). IMC can promote nutrient transport, blood vessel ingrowth, and osteogenic cell migration throughout the scaffold (Liao et al, ; Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations